Pengaruh Bimbingan Karir dengan Teknik Modelling untuk Meningkatkan Perencanaan Karir Mahasantri Pondok Pesantren Al-quran Ibnu Katsir 1 Putra Jember - Muhid Kumarul Amin; Wahid Suharmawan; Ika Romika Mawaddati (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2024)
Career guidance involves providing guidance to prepare individuals to face challenges in the workforce, choosing specific fields or positions, and providing the knowledge and skills needed to perform tasks effectively. Career planning is a process that involves understanding oneself, available opportunities, potential obstacles, and the consequences of each choice made in order to achieve set career goals. The aim of this research is to explore whether the implementation of career guidance using modeling techniques can enhance the career planning of students at Pondok Pesantren Al-Quran Ibnu Katsir 1 Putra Jember. This study employs a quantitative method with a pre-experimental design called One Group Pre-test Post-test. The population consists of 65 individuals, and the sample comprises 20 students. Data were collected through observation, interviews, and questionnaires, which were then validated and tested for reliability before being disseminated. Data analysis was conducted using the Wilcoxon Match Pairs Test. From the Wilcoxon test results, a value of Asymsig. (2 tailed) was found to be 0.018, indicating that the alternative hypothesis is accepted because it is smaller than 0.05. Thus, it can be concluded that the implementation of career guidance using modeling techniques has a positive impact on enhancing the career planning of students from the 2021 cohort at Pondok Pesantren Al-Quran Ibnu Katsir 1 Putra Jember